The impact of focused corrective feedback and meta-linguistic explanation on L2 composition writing / Jeanice Stephen Jeyaraj - Jeanice Stephen , Jeyaraj (2019)

(untitled)
This mixed-method study investigated the effectiveness of focused corrective feedback and meta-linguistic explanation on the accuracy of subject-verb-agreement among learners of second language. For the quantitative inquiry, 28 learners were recruited and pre-test and post-test were administered over a 10 week period. For the qualitative inquiry, this study attempted to explore learners’ perceptions towards the provision of focused corrective feedback and meta-linguistic explanation by conducting semi-structured interviews with selected participants. From the quantitative inquiry, learners managed to retain their accuracy performance because significant improvement was shown in the delayed post-test compared to the score means in the pre-test and immediate post-test. Findings from the qualitative inquiry revealed that learners found the feedback and meta-linguistic explanation effective and helpful in enhancing their new piece of writing. One of the prevalent limitations was this study did not include a control group. In order to explore the efficacy of corrective feedback, there should be a control group to compare the results.